The Effectiveness of Virtual Reality (VR) on Preoperative Anxiety in Elective Surgery Patients Under General Anesthesia: A Systematic Review - Eva Yulianti; I Made Kariasa; Agung Waluyo; Dikha Ayu Kurnia (Jurnal Ipteks Terapan, 2023)
Background: The high prevalence of preoperative anxiety is associated with adverse postoperative outcomes such as pain, prolonged recovery, impaired wound healing, prolonged hospitalization, increase in the need for anesthetic drugs, prolonging the duration of anesthesia, one of the possible causes of canceling surgeries and death. One of the current non-pharmacological interventions to reduce preoperative anxiety is Virtual Reality (VR). This systematic review aims to evaluate the effectiveness of virtual reality on preoperative anxiety in elective surgery patients under general anesthesia. Methods: This study was a systematic review of randomized controlled trials (RCTs) and prospective cohort study. A systematic was conducted using ClinicalKey, Clinicalkey for Nursing, EBSCOhost, Proquest, ScienceDirect, Scopus, Pubmed, SpringerLink, and the Cochrane library, and using keywords and Boolean Operators. Search for English and publish from January 2018 to December 2022. Results: Eight studies were found eligible for inclusion, seven studies showed a significant decrease in perioperative anxiety levels in patients with the use of virtual reality in providing education and distraction compared to the standard care group. Conclusion: The findings of the systematic review show that Virtual reality is an effective education and distraction method to reduce preoperative anxiety in elective surgery patients under general anesthesia..